Gender Justice in the Concept of Iddah: A Contextual Reading of Al-Kasani’s Thought for Working Women in Indonesia - Wahyu Abdul Jafar; Alamsyah Alamsyah; Maimun Maimun; Muhammad Zaki; Siti Mahmudah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The concept of iddah in Islam is a fundamental aspect of family law, serving as a transitional period for women following divorce or the death of a husband. However, modern social and economic developments have led to an increasing number of women pursuing careers, raising questions about the relevance of iddah regulations in contemporary contexts. This study aims to analyze the concept of iddah for Working Women based on the thoughts of Imam Ala’uddin Al-Kasani, examining it through the lens of gender and marital dynamics in the context of Islamic family law in Indonesia. This research employs a qualitative approach with a literature analysis of Al-Kasani’s seminal work, Bada’i as-Sana’i fi Tartib as-Syarai’. Additionally, it compares his views with contemporary scholars and the policies of Islamic family law in Indonesia. The findings reveal that Al-Kasani emphasized iddah as a mechanism to protect women’s rights, particularly concerning lineage and financial security. However, in the context of women in modern careers, the application of iddah needs to be reassessed, considering women’s economic roles and the evolving dynamics of marital relationships. This study concludes that the recontextualization of iddah should be carried out with a focus on gender justice while preserving the maqashid shariah (higher objectives of Islamic law) within family law. Therefore, a more inclusive and contextual reinterpretation of Islamic legal rulings is necessary to ensure that iddah remains relevant to the lives of modern Muslim women in Indonesia. This research contributes to the academic discourse by offering a fresh perspective on the concept of iddah within a more dynamic social framework. A gender-just recontextualization of iddah can be a reference for developing a more inclusive and adaptive Islamic family law in Indonesia